Expression of LINC00847 in Peripheral Blood Mononuclear Cells of Children with Asthma and Its Prediction between Asthma Exacerbation and Remission - Jiaying Hu; Zhike Wang; Suzhen Han; Kai Chen (Genetics Research)
Objective. Asthma is defined as a heterogeneous disease that is usually characterized by chronic airway inflammation. Long noncoding RNAs play important roles in various biological processes including inflammation. To know more about the relationships between lncRNAs and asthma, we sought to the role of LINC00847 in peripheral blood mononuclear cells (PBMCs) of children with asthma exacerbation or asthma remission. Methods. Microarray analysis was performed on GSE143192 and GSE165934 datasets to screen differentially expressed lncRNAs (DElncRNAs) in human PBMCs between asthma patients and normal controls. LINC00847 was selected from DElncRNAs in human PBMCs between asthma patients and normal controls for further investigation. The expression levels of LINC00847 were quantified in PBMCs collected from 54 children with asthma exacerbation, 54 children with asthma remission, and 54 healthy children by real-time qPCR. The forced expiratory volume in the first second in percent predicted values (FEV1%), ratio of forced expiratory volume in 1 second to forced vital capacity (FEV1/FVC), and peak expiratory flow rate (PEF%) were tested for evaluation of lung function. The concentration of immunoglobulin E (IgE) and eosinophil count was examined. The serum levels of interleukin-4 (IL-4), interferon-γ (IFN-γ), and IL-17A were determined by the ELISA method. Results. The expression level of LINC00847 in PBMCs of asthma exacerbation children was remarkably higher than that in PBMCs of asthma remission children and healthy children (p<0.001); the expression level of LINC00847 in PBMCs of asthma remission children was notably higher than that in PBMCs of healthy children (p<0.001). Pearson correlation analysis revealed that the expression levels of LINC00847 in PBMCs of asthma children were negatively correlated with FEV1% (r = −0.489), FEV1/FVC (r = −0.436), PEF% (r = −0.626), and IFN-γ level (r = −0.614) of asthma children, but positively correlated with IgE concentration (r = 0.680), eosinophil count (r = 0.780), IL-4 (r = 0.524), and IL-17A (r = 0.622) levels. When LINC00847 expression was used to distinguish asthma exacerbation from asthma remission, a 0.871 AUC (95% CI: 0.805–0.936) was yielded with sensitivity of 79.63% and specificity of 77.78%. Conclusion. The study demonstrates that increased LINC00847 expression may be associated with the development and progression of asthma, possibly serving as a novel biomarker for predicting asthma exacerbation from asthma remission.